Coumarin-Based Hybrid Molecules in Modern Drug Design: Chemistry, Biological Activities, and Future Perspectives - Anuj Kumar Sharma; Mukul Kumar Rana; Hanumant Ji Sharma; Shivam Garg; KM Anjali (International Journal of Scientific Research in Science and Technology, 2026)
Coumarin represents a versatile heterocyclic scaffold that has attracted considerable attention in medicinal chemistry due to its broad spectrum of biological activities and structural adaptability. In recent years, the concept of molecular hybridization has been widely applied to the coumarin nucleus to generate hybrid molecules with enhanced pharmacological potential. Coumarin-based hybrids are formed by integrating the coumarin framework with other biologically active pharmacophores such as chalcones, triazoles, quinolines, and benzimidazoles, resulting in compounds capable of interacting with multiple biological targets. Numerous studies have demonstrated that these hybrid molecules exhibit significant biological activities, including anticancer, antimicrobial, anti-inflammatory, antioxidant, antiviral, and antitubercular effects. The biological performance of coumarin hybrids is strongly influenced by structural factors such as functional group modifications and substitution patterns, which determine their interactions with enzymes, receptors, and cellular signaling pathways. Structure–activity relationship studies have provided valuable insights into the optimization of these compounds for improved potency and selectivity. However, challenges related to toxicity, bioavailability, and synthetic complexity remain important considerations in the development of coumarin-based therapeutics. This review highlights recent advances in the design, synthesis, and biological evaluation of coumarin hybrid molecules and discusses their potential as promising candidates for future drug discovery. The integration of modern computational approaches and innovative synthetic strategies is expected to further accelerate the development of novel coumarin-based drugs with improved therapeutic profiles.
Keywords: Coumarin hybrids; molecular hybridization; drug design; anticancer activity; antimicrobial activity; structure–activity relationship (SAR)